A fractal model on predicting the water vapor permeability of autoclave aerated concrete (AAC) with various porosities. (March 2020) - Tian, Shuai-Qi; Fan, Li-Wu; Yu, Zi-Tao; Ge, Jian
Highlights: A fractal model for predicting the water vapor permeability of AAC was established. The key parameters in this model were the porosity and the pore size distribution. The RH dependence on the predicted permeability was revealed by the fractal model. This fractal model was validated to be feasible in the medium RH range of 30%–60%. Abstract: In this work, the water vapor permeability of autoclave aerated concrete (AAC) with various porosities, as a typical porous building material, were predicted based on the fractal theory, with emphasis on the effects of relative humidity (RH). The tortuosity fractal dimensions were first determined based on the porosities and pore sizes of the various AAC samples. The water vapor permeabilities were then predicted based on the determined tortuosity fractal dimensions, porosities, pore sizes and the isothermal adsorption curves. The model was validated by comparing the predicted results with experimental data. Results indicated that in this model, the porosity and pore size of the AAC samples have considerable effects on the predicted water vapor permeability. For all types of AAC, the predicted water vapor permeabilities were found to agree well with experimental data in the medium RH range of 30%–60% with the maximum deviation being less than 15%. In the low RH range below 30%, the water vapor permeabilities were underestimated, mainly due to the disconnected water vapor phase in the realistic scenario. In conclusion, this fractal model can be utilized to predict the water vapor permeability of AAC with various porosities and pore size distributions in the medium RH range of 30%–60%.